A comprehensive evaluation of pathogenic mutations in primary cutaneous melanomas, including the identification of novel loss-of-function variants - Ticha, Ivana; Hojny, Jan; Michalkova, Romana; Kodet, Ondrej; Krkavcova, Eva; Hajkova, Nikola; Nemejcova, Kristyna; Bartu, Michaela; Jaksa, Radek; Dura, Miroslav; Kanwal, Madiha; Martinikova, Andra S; et al. (Scientific reports, 2019)
The most common histological subtypes of cutaneous melanoma include superficial spreading and nodular melanoma. However, the spectrum of somatic mutations developed in those lesions and all potential druggable targets have not yet been fully elucidated. We present the results of a sequence capture NGS analysis of 114 primary nodular and superficial spreading melanomas identifying driver mutations using biostatistical, immunohistochemical and/or functional approach. The spectrum and frequency of pathogenic or likely pathogenic variants were identified across 54 evaluated genes, including 59 novel mutations, and the newly identified TP53 loss-of-function mutations p.(L194P) and p.(R280K). Frequently mutated genes most commonly affected the MAPK pathway, followed by chromatin remodeling, and cell cycle regulation. Frequent aberrations were also detected in the genes coding for proteins involved in DNA repair and the regulation and modification of cellular tight junctions. Furthermore, relatively frequent mutations were described in KDR and MET, which represent potential clinically important targets. Those results suggest that with the development of new therapeutic possibilities, not only BRAF testing, but complex molecular testing of cutaneous melanoma may become an integral part of the decision process concerning the treatment of patients with melanoma.
Keywords: nádorový supresorový protein p53; senioři; Genetic Predisposition to Disease; Cell Cycle; MAP Kinase Signaling System; senioři nad 80 let; mutace ztráty funkce; Skin Neoplasms; Melanoma; Middle Aged; mužské pohlaví; Tumor Suppressor Protein p53; Adult; mladý dospělý; buněčný cyklus; Biomarkers, Tumor; Aged, 80 and over; Young Adult; ženské pohlaví; nádorové biomarkery; melanom; Loss of Function Mutation; Humans; nádory kůže; High-Throughput Nucleotide Sequencing; Proto-Oncogene Proteins B-raf; oprava DNA; Tight Junctions; lidé středního věku; frekvence genu; restrukturace chromatinu; vysoce účinné nukleotidové sekvenování; protoonkogenní proteiny B-Raf; MAP kinasový signální systém; Gene Frequency; dospělí; Melanoma, Cutaneous Malignant; maligní melanom kůže; genetická predispozice k nemoci; DNA Repair; Female; Aged; těsný spoj; lidé; Male; Chromatin Assembly and Disassembly